(untitled) (Ecological Bulletin of Kryvyi Rih District, 2021)
The area and quality condition of green spaces are recognized as an international indicator of the compliance of the city’s infrastructure with the principles of sustainable development. The multifunctionality of green spaces determines their paramount, strategic importance in the improvement of industrial cities due to the ability to neutralize and reduce the adverse impact of various factors of anthropic and technogenic origin, create comfortable conditions for recreation, and ensure the constitutional rights of citizens to live in a favorable environment. Coniferous species play a special role in the composition of the city’s green spaces. Biological, ecological, sanitary and hygienic, decorative features and properties of these plants determine their high economic value, which is a prerequisite for the relevance of detailed research aimed at a comprehensive study of the taxonomic fund of coniferous greenery of certain functional areas of Kryvyi Rih to optimize them. Studies of the taxonomic composition of conifers have been implemented within green areas of public and limited use. In the course of the work 33 sections of Metallurgical and 25 sections of the description of Dovhyntsivsky administrative-territorial districts of the city were inspected. The results of the analysis show a narrow range of species of conifers used in landscaping. Thus, only 10 species of conifers, which are representatives of 6 genera and 3 families, were registered within the study areas. The composition of public green areas is more diverse in terms of assortment. Here are nesting groups of Picea abies (L.) Karst., Thuja occidentalis L., Pinus sylvestris L., available alleys with Picea abies (L.) Karst. and Picea pungens Engelm., Pinus sylvestris L. In the territories of health care institutions there are group plantings with Thuja occidentalis L., Picea abies (L.) Karst. and Picea pungens Engelm., Pinus sylvestris L. It should be noted that in the green areas of limited use, located in the territories of health care institutions, conifers, even in a small number of taxa, are always present. The smallest diversity of species is registered in the green areas of limited use of educational institutions. Representatives of families Pinaceae and Cupressaceae, recorded in green plantations of different functional purpose, became the most widespread. The analysis of the research results testifies to the need to expand the range of coniferous green plants of general and limited use due to the species already adapted to the specific conditions of the industrial region using the capabilities of the Kryvyi Rih Botanical Garden of the NAS (National Academy of Sciences) of Ukraine. Promising for landscaping can be considered Cryptomeria japonica Thunb. ex L.f., Juniperus squamata Lamb., Juniperus procumbens, Pinus nigra ssp. pallasiana, Pseudotsuga menziessii (Mirb) Franco., Pinus strobus L., Abies alba Mill., Picea omorica (Panc.) Purkyne, Chamaecyparis lawsoniana Parl.